Application of Traditional Chinese Medicine health preservation exercise in the rehabilitation treatment of patients with late stage of lumbar disc herniation (中医养生操在腰椎间盘突出症后期患者康复治疗中的应用) - ZHAO Xiangli (赵祥丽); WANG Tingting (王婷婷) (Association of Integrative Nursing, 2021)
Objective To investigate the effect of Traditional Chinese Medicine (TCM) health preservation exercise in the rehabilitation treatment of patients with late stage of lumbar disc herniation (LDH). Methods Totally 67 patients with late stage of LDH were enrolled in the study. TCM health preservation exercise was carried out during the rehabilitation treatment, and its effect on symptom relief was evaluated. Results Low back pain was significantly improved in patients after intervention. According to the Japanese Orthopaedic Association (JOA) Score, the total effective rate of TCM health preservation exercise was 97. 01%(65/67). Conclusion The TCM health preservation exercise is potentially effective to relief the symptom and reduce the intensity of low back pain in patients with late stage of LDH. (目的 探讨腰椎间盘突出症后期患者康复治疗中采用中医养生操的应用效果。方法 选取67例腰椎间盘突出症后期患者为研究对象, 康复治疗过程中采用中医养生操进行干预, 采用视觉模拟评分(VAS)评估患者疼痛症状改善情况, 评价干预效果。结果 干预后, 患者疼痛症状改善明显。依据日本骨科协会(JOA)评估治疗分数评分评价干预效果, 总有效率为97. 01%(65/67)。结论 在腰椎间盘突出症后期患者康复治疗中采用中医养生操, 能够明显改善疾病症状, 降低患者疼痛感, 对促进患者康复、提高其生活质量具有积极意义。)